RESEARCH PHOTOSYNTHESIS EFFICIENCY OF DIFFERENT SOURCES OF OPTICAL RADIATION - Chervinsky, L; Lutsak, Y. (Energy and Automation, 2016)
A comparative analysis of the various sources of fotosynthesis radiation early hothouse for growing crops. Confirmed efficiency LED illuminators.